2017
DOI: 10.1038/s41467-017-01231-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinesis requires localized β-actin filament production by an actin isoform specific nucleator

Abstract: Cytokinesis is initiated by the localized assembly of the contractile ring, a dynamic actomyosin structure that generates a membrane furrow between the segregating chromosomal masses to divide a cell into two. Here we show that the stabilization and organization of the cytokinetic furrow is specifically dependent on localized β-actin filament assembly at the site of cytokinesis. β-actin filaments are assembled directly at the furrow by an anillin-dependent pathway that enhances RhoA-dependent activation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 54 publications
5
79
1
Order By: Relevance
“…Notably, our data do not exclude a role for Rho1 in forming the Dia-based actin bundles of the caps, and indeed, Rho1 inhibitor injection reduces cap growth (Cao et al, 2010). It is possible that Par-1 could help Rho1 relieve Dia autoinhibition (Chen et al, 2017;Higashi et al, 2010), or that Par-1 could promote the bundling and/or stabilization of actin filaments induced by Rho1 and Dia. Either mechanism would be particularly important for Dia-based actin bundles in the cap, where, based on the distributions of the Rho1-GTP sensor (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, our data do not exclude a role for Rho1 in forming the Dia-based actin bundles of the caps, and indeed, Rho1 inhibitor injection reduces cap growth (Cao et al, 2010). It is possible that Par-1 could help Rho1 relieve Dia autoinhibition (Chen et al, 2017;Higashi et al, 2010), or that Par-1 could promote the bundling and/or stabilization of actin filaments induced by Rho1 and Dia. Either mechanism would be particularly important for Dia-based actin bundles in the cap, where, based on the distributions of the Rho1-GTP sensor (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…Additional previously unappreciated aspects of the cHL genetic signature include the likely role of ARID1A alterations in driver mutational events ( Figure 4C), 69 the predominant Aging mutational signature 95 in this young patient population ( Figure 2), and potential genetic mechanisms of defective cytokinesis 2,3,60,61 in multinucleated HRS cells ( Figure 5; supplemental Figure 3).…”
Section: Discussionmentioning
confidence: 95%
“…[57][58][59] In murine models, Ga13 deficiency was associated with GC B-cell expansion and dissemination, enhanced AKT signaling, and an increased incidence of B-cell lymphomas. 58,59 In these multinuclear HRS cells, which are postulated to have defective RHOA-and b actin-dependent cytokinesis, [1][2][3]60 Table 4). 6 CLUMPS revealed additional alterations in EEF1A1 (supplemental Figure 3A; supplemental Tables 3 and 4), 6 which encodes a translation factor implicated in chromosome condensation and tetraploid cell formation.…”
Section: Ccgs In Chlsmentioning
confidence: 99%
“…Formation of the contractile ring requires activation of the small GTPase RhoA by the Guanine Nucleotide Exchange Factor (GEF), ECT-2 (Basant and Glotzer, 2018). Active, GTP-bound RhoA assembles and activates components of the actomyosin-based ring, such as diaphanous-related formin that facilitates the assembly of actin filaments (Otomo et al, 2005;Watanabe et al, 2008;Piekny et al, 2005;Chen et al, 2017), and Rho-Kinase (ROCK), which activates nonmuscle myosin II to power ring constriction (Kosako et al, 2000;Amano et al, 1996). Optogenetic manipulation of RhoA activity showed that local activation of RhoA on the cell membrane is sufficient to drive cleavage furrow initiation independent of cell cycle stage (Wagner and Glotzer, 2016).…”
Section: Introductionmentioning
confidence: 99%